Reversible ADP-ribosylation of RNA - Munnur, D; Bartlett, E; Mikolcevic, P; Kirby, I; Rack, J; Mikoc, A; Cohen, M; Ahel, I (Oxford University Press, 2019)
ADP-ribosylation is a reversible chemical modification catalysed by ADP-ribosyltransferases such as PARPs that utilize nicotinamide adenine dinucleotide (NAD+) as a cofactor to transfer monomer or polymers of ADP-ribose nucleotide onto macromolecular targets such as proteins and DNA. ADP-ribosylation plays an important role in several biological processes such as DNA repair, transcription, chromatin remodelling, host-virus interactions, cellular stress response and many more. Using biochemical methods we identify RNA as a novel target of reversible mono-ADP-ribosylation. We demonstrate that the human PARPs - PARP10, PARP11 and PARP15 as well as a highly diverged PARP homologue TRPT1, ADP-ribosylate phosphorylated ends of RNA. We further reveal that ADP-ribosylation of RNA mediated by PARP10 and TRPT1 can be efficiently reversed by several cellular ADP-ribosylhydrolases (PARG, TARG1, MACROD1, MACROD2 and ARH3), as well as by MACROD-like hydrolases from VEEV and SARS viruses. Finally, we show that TRPT1 and MACROD homologues in bacteria possess activities equivalent to the human proteins. Our data suggest that RNA ADP-ribosylation may represent a widespread and physiologically relevant form of reversible ADP-ribosylation signalling.